065 Spiralling down the spitoon: a novel approach to improve safe dental sedation. (5th November 2017) - Hughes, Gareth; Baker, J; Cocking, C
Abstract : Background: There is increasing concern regarding the lack of standardisation of sedation within dental practice. This has potential implications for patient safety. The 2015 document 'Standards for Conscious Sedation in the Provision of Dental Care' 1 attempted to provide a unified template to address these concerns. This stresses key standards to ensure patient safety coupled with validated and continuing education. Subsequent to this, a joint letter from all UK CDOs, examined how best to practically implement the reports' recommendations. 2 Educational Programme within the East Midlands, Derby Teaching Hospitals NHS Foundation Trust has collaborated to develop a programme aimed at improving sedation within dentistry. The Post Graduate Dental Deanery in conjunction with local simulation faculties has created a four day course. This is taught by a broad faculty including experts in dental and general sedation in addition those conversant in the management of medical emergencies. The programme utilises a bespoke simulated dental environment in which candidates experience a focused educational program and then undertake individual assessments with a comprehensive debrief. The course content comprises of theory coupled with skills stations, simulated scenarios, with a key emphasis on human factors. The recognition and management of potential complications occurring during dental sedation rather than a simplistic 'recipe' driven approach are addressed. The course was piloted at The Royal Derby Hospital with regional dental foundation trainees. The efficacy of the course was assessed by an externally commissioned chartered Occupational Psychology Consultancy with a view to objective validation. They interviewed participants before, during and after the course assessing the educational experience with well-established methods. Participants undertook an individual simulated emergency occurring during a sedation event. They received individual and group feedback following this. Conclusions and Recommendations: Participants felt that the clinical content was pitched at an appropriate level. 91% felt individual feedback to be highly beneficial, compared to 82% who felt similarly towards group feedback. It was felt that 1:1 feedback could be improved by having a formalised structure. During group feedback it was additionally felt that human factors could have been explored in greater depth. Both these issues may be products of time constraints, alleviated in the future by a reduced number of participants. The training increased overall self -efficacy scores for all except one participant. There were specific self-efficacy gains in managing emergencies, assessing patients and planning/performing conscious sedation. Recommendations will be addressed as part of future planning. References: . 'Standards for Conscious Sedation in the Provision of Dental Care'. Report of the intercollegiate advisory committee for sedation in dentistry 2015. . Letter from the offices of The Chief Dental Officers 2016. England, Northern Ireland, Scotland, & Wales.